La Coordinación Espacial en el desarrollo de la Lateralidad en los niños de 4-5 años en la Unidad Educativa “Fernando Daquilema”del cantón Riobamba, provincia de Chimborazo. periodo lectivo 2015-2016. - Sinaluisa Sagba, Aida Isabel (2016)
This research work carried out in the Education Unit “Fernando Daquilema” In Riobamba county, Chimborazo province 2015-2016 academic year, focusing research on “The spatial coordination in the development of laterality in children 4-5 years. In the development work it is to show that knowledge of the notions of spatial coordination and laterality is of great importance since it is a precondition for the start of the formal learning process, factors that depend on children to begin their school years, and avoid the presence of difficulties in the process of school learning, such as poor coordination, confusion, alterations, confusions in letters, syllables, words and numbers, and thus ensure that a child is placed at the appropriate time and space. Through authors and researcheers diversity of concepts and methodological contributions which supports the research subject was obtained, so that for the development of fieldwork descriptive research under a non-experimental statistical design was applied, because there was no manipulation in concerning the study variables, we worked with the total population in a number of 35 students, 20 girls and boys, for data collection a tab observation was used to children of the institution. After obtaining the data we proceed to tabulating them through the Microsoft Excel program that allows us to know in percentage each of the indicators of the questions raised in the observation sheet, and thus make decisions or grant recommendations in an accurate and timely way, Regarding the results of the research may show that in the analysis of interpretation of results was achieved that in the alternative acquired is the lowest percentage regarding the assessment, enabling mention that there is the problem, therefore the contribution of strategies through motor activities, strengthen such a drawback, therefore as a contribution to improving variable spatial coordination and laterality in children is the implementation of activities to stimulate the development of laterality involving the partial or total movement of the human body.